Sosialisasi Peranan Dan Penggunaan Microsoft Word Untuk Penguatan Pendidikan Bagi Murid SD Santa Theresia III - Gabris, Giwinfill; Julia (Indonesian Journal of Dedication and Educations, 2024)
Abstract : With the rapid development of the times and the increasing use of technology, many companies and schools, many students are required to use technology as an additional learning medium at home after finishing studying at school. The development of this technology is very pending with the emergence of several platforms, one of which is Microsoft Word. The purpose of this activity is the role and importance of using Microsoft to strengthen education and provision in the future in the world of work and school. The MBKM Teaching Assistance Program with the application of this technology lasts for 4 months starting from July 10 – October 29, 2023. The application of technology in the world of teaching assistance helps the role of learning in Santa Thersia III Elementary School. The Development of the Times, Technology Development, Microsoft Word and Teaching Assistance